Pengaruh Senam Lansia Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi di Desa Salu Paremang Selatan Kecamatan Kamanre Kabupaten Luwu - Musfah, A. Wardah; Datu, Natalia; Asri, Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The Effect of Elderly Exercise on Reducing Blood Pressure in Hypertension Sufferers in South Salu Paremang Village, Kamanre District, Luwu Regency in 2023." Hypertension is a medical condition with a high prevalence, where global hypertension cases are estimated at 22% of the total world population. In 2015 it was estimated that 1 in 4 men and 1 in 5 women suffered from hypertension (WHO, 2019). Based on data obtained from the Kamanre Community Health Center in Luwu Regency in 2022, the prevalence of the elderly population is 107 people, of which 64 elderly people suffer from hypertension. The high incidence of hypertension requires health workers to take preventive measures. In addition to using conventional treatment, hypertension in the elderly can also be treated with non-conventional treatment, one of which is elderly exercise. The aim of this research is to determine the effect of elderly exercise on reducing blood pressure in hypertension sufferers in South Salu Paremang Village, Kamanre District, Luwu Regency in 2023. This research design uses a quantitative design with a (quasi-experimental) approach with a one group pretest posttest design. The sample in this study was 21 elderly people aged 45 years and over. The results showed that most of the patients were 17 women (81.0%) and 4 men (19.0%). The average age of 41-50 years is 14 people (66.7%). The average systolic blood pressure before and after elderly exercise shows a Z value of -4.078 and the average diastolic blood pressure before and after elderly exercise shows a Z value of -3.375. This is based on the results of the Wilcoxon Signed Rank Test showing that there is an effect of elderly exercise on patients on reducing blood pressure (?=0.000).